ISLAM AND RADICALISM IN SOCIAL LEARNING THEORY PERSPECTIVE - Sri Rejeki (TAWASUT, 2013)
Islam and radicalism are two very different things. It is then unjustified to emerge the term "Islamic radicalism" since it will reduce all the teachings of Islam itself. This is also because every religion has never taught its followers to act radically, but it doctrinally teaches kindness and peace. Therefore,  the emergence of radicalism on behalf of religion (Islam) needs to be explored in detail to deliver a comprehensive and balanced enlightenment. This paper seeks to review and provide an analysis based on social learning theory related to radicalism actor who has a particular community. This community undoubtedly becomes the source of forming a radical under-standing of Islam as well. Of the social learning theory, it is found that one of several causes of it is an improper learning process form in which the community provides a model of action or an incorrect understanding about the meaning of jihad in Islam.Keywords:   Islam, radicalism, causes of radicalism, social learning theory, improper learning process